2020
DOI: 10.3390/en13092124
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Renewable and Nuclear Energy Consumption on Decoupling Economic Growth from CO2 Emissions in Spain

Abstract: This study examines the relationship between renewable and nuclear energy consumption, carbon dioxide emissions and economic growth by using the Granger causality and non-linear impulse response function in a business cycle in Spain. We estimate the threshold vector autoregression (TVAR) model on the basis of annual data from the period 1970–2018, which are disaggregated into quarterly data to obtain robust empirical results through avoiding a sample size problem. Our analysis reveals that economic growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 62 publications
2
25
1
Order By: Relevance
“…The results are consistent with Zoundi [32], who suggests that renewable energy and GDP negatively and positively affect CO 2 emissions, respectively, and who shows findings similar to this study for population growth. These findings are also similar to those obtained by Dong et al [1] and Shuai et al [50] for the case of Africa, and are consistent with results estimated by Mariola et al [51], which showed that renewable energy negatively affects emissions, while economic growth increases emissions, in the case of Spain. In contrast, renewable energy and population growth significantly and positively affect GDP.…”
Section: Ccemg Estimate Resultssupporting
confidence: 92%
“…The results are consistent with Zoundi [32], who suggests that renewable energy and GDP negatively and positively affect CO 2 emissions, respectively, and who shows findings similar to this study for population growth. These findings are also similar to those obtained by Dong et al [1] and Shuai et al [50] for the case of Africa, and are consistent with results estimated by Mariola et al [51], which showed that renewable energy negatively affects emissions, while economic growth increases emissions, in the case of Spain. In contrast, renewable energy and population growth significantly and positively affect GDP.…”
Section: Ccemg Estimate Resultssupporting
confidence: 92%
“…Notably, the findings from the literature on the effects of clean energy consumption (renewable and nuclear) on both carbon emissions and economic growth are mixed and depend on the method used, the country coverage, and the time periods. Moreover, most studies consider the impact of clean energy consumption on emissions and economic growth using a linear model with few exceptions [66][67][68][69]. For instance, the authors in [67] used the panel threshold regression method and found that the impact of renewable energy consumption on economic activity depends on the amount of renewable energy used, i.e., this impact is positive and significant only for countries surpassing a certain threshold of renewables.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Today the world economy is handling an economic crisis caused by the pandemic of a new coronavirus infection (COVID- 19), announced by the WHO, as well as by fluctuations in the international energy market and by the development of "green energy" [1]. The crisis has been named the "2020 crisis".…”
Section: Introductionmentioning
confidence: 99%